Start by finding the first differences of the terms:

\[

\begin{aligned}

&\text { For } T_{1} \text { and } T_{2}: \quad-25-(-13)=-12 \\

&\text { For } T_{2} \text { and } T_{3}: \quad-43-(-25)=-18 \\

&\text { For } T_{3} \text { and } T_{4}: \quad-67-(-43)=-24

\end{aligned}

\]

Now calculate the second differences:

\[

\begin{array}{ll}

\text { first two differences: } & -18-(-12)=-6 \\

\text { next two differences: } & -24-(-18)=-6

\end{array}

\]

In this case, the second differences are equal to each other, with a value of \(-6\).